GAMBARAN PENOLAKAN MASYARAKAT TERHADAP PUNGSI LUMBAL DI BAGIAN NEUROLOGI BLU RSUP. PROF. DR. R.D. KANDOU MANADO - Pasomba, Selvyani; Khosama, Herlyani; Sampoerno, Junita M.P. (e-CliniC, 2013)
Abstract: The examination of cerebrospinal fluid obtained by a lumbar puncture is important in the diagnosis of CNS infection. There have been no reports of refusals of lumbar punctures in Manado. This study is a descriptive preliminary using interviews and questionnaires. The subjects were all patients or families of patients in the inpatient unit at the Department of Neurology BLU. Prof. Dr. R. D. Kandou Manado in November 2012. The results showed that of the total number of 60 respondents, 27 (45%) under advice, agreed to undergo lumbar punctures; 30 (50%) refused, and 3 (5%) were not able to decide and thus abstained. While 93.3% of respondents knew the definition and indications of lumbar puncture, 86.7% refused eventhough they knew that the lumbar puncture procedure was important in the management of the disease; 86.7% assumed that the lumbar puncture was a dangerous procedure; 80% felt unsure enough to refuse; and 86.7% were afraid to have the lumbar puncture procedure done. All respondents knew that lumbar puncture had complications. Conclusion: nearly all respondents who refused knew that the lumbar puncture procedure is important in the management of the disease, yet they assumed the lumbar puncture was dangerous, uncomfortable, and felt fearful. Keywords: lumbar puncture, neurology, refusal description, society. Abstrak: Pemeriksaan cairan serebrospinal yang diperoleh melalui tindakan pungsi lumbal penting untuk mendiagnosis infeksi susunan saraf pusat. Meskipun demikian, sering terjadi penolakan terhadap pemeriksaan ini. Sampai saat ini belum ada laporan tentang gambaran penolakan pungsi lumbal di Manado. Penelitian ini bersifat deskriptif dengan wawancara menggunakan kuesioner. Subjek penelitian ialah semua pasien atau keluarga pasien di ruang rawat inap Bagian Neurologi BLU RSUP. Prof. Dr. R.D. Kandou Manado bulan November 2012. Hasil penelitian memperlihatkan jumlah responden sebanyak 60 orang, 27 (45%) setuju jika seandainya disarankan untuk menjalani pungsi lumbal, 30 (50%) menolak, dan tiga (5%) tidak dapat memutuskan setuju atau menolak (abstain). Sebanyak 93,3% responden mengetahui definisi dan indikasi pungsi lumbal, 86,7% responden yang menolak menganggap pungsi lumbal penting dalam penatalaksanaan penyakit, 86,7% menganggap pungsi lumbal merupakan tindakan yang berbahaya, 80% responden merasa tidak nyaman, dan 86,7% takut terhadap pungsi lumbal. Simpulan: hampir seluruh responden yang menolak mengetahui bahwa tindakan pungsi lumbal penting dalam penatalaksanaan penyakit, dan menganggap pungsi lumbal sebagai tindakan berbahaya, tidak nyaman dan merasa takut pada tindakan ini. Kata kunci: pungsi lumbal, neurologi, gambaran penolakan, masyarakat.